Effect of the surface morphology of solidified droplet on remelting between neighboring aluminum droplets - Yi, Hao; Qi, Lehua; Luo, Jun; Zhang, Daicong; Li, Hejun; Hou, Xianghui (Elsevier, 2018)
Good metallurgical bonding between neighboring droplets is essential in droplet-based 3D printing. However, although the mechanism of remelting has clearly been mastered, cold laps are still common internal defects of formed parts in uniform aluminum droplets deposition manufacturing, which is due to the overlook of the surface morphologies of solidified droplets. Here, for the first time, the blocking effect of ripples and solidification angles on the fusion between droplets is revealed. To investigate the detailed process of remelting, a 3D numerical model was developed, basing on the volume of fluid (VOF) method. Experiments and simulations show that the remelting process between neighboring droplets can be divided into two stages according to the transient contact between the second droplet and the substrate. In the first stage, a non-intuitive result is observed that cold laps can also be formed even if the remelting conditions are satisfied in theory. Ripples on the surface of previously-deposited droplet block its direct contact with the new-coming droplet. In the second stage, cold laps on bottom surface are formed due to incomplete filling of liquid metal when the solidification angle is greater than 90°. Furthermore, these cold laps are difficult to be completely avoided by improving the temperature parameters. To address this problem, a novel strategy of decreasing the thermal conductivity coefficient of the substrate is proposed. This method effectively promotes remelting between droplets by eliminating ripples and decreasing solidification angles.